Matemática financeira do ensino médio com o uso da calculadora HP 12c em Smartphones - SILVA, Patrícia da Silva Vaz da (2023)
Financial Mathematics plays an important role in people's lives, for this reason this work aims to propose to high school teachers the use of DICTs (Digital Information and Communication Technologies) in the teaching of financial mathematics, in order to understand how financial Technological resources can help in the teachinglearning process of high school financial Mathematics content. From this, it was decided to use a smartphone application for the HP 12C financial calculator, as a didactic resource. For this, a bibliographic review of works aimed at this context was carried out, prioritizing those that used technological resources such as: calculator and applications for teaching Financial Mathematics in schools. Therefore, we approach basic concepts such as interest, percentage, interest rates and subjects such as capitalization schemes, equivalent and proportional rates, discounts and amortization systems, all of these in order to cover the daily lives of students, working on issues such as loans , overdraft, cash or installment purchases, use of credit card, debt amortization and others. In this way, sequential activities were elaborated to the contents containing contextualized problem-situations, followed by solutions without and with the use of the HP 12C application.